Education as alternative to violence: child soldiers in Sierra Leone - Chema Caballero (FahrenHouse, 2012)
Education plays a key role in the process of rehabilitation and reintegracion of child soldiers and helps them to overcome the psysologial and moral impact of the war. Children see education as their gateway to a different life away from the violence and suffering they experienced during the years lived with the armed grups. The desire to change life makes children strive in this activity devouting great effort to stand out above the rest of their classmates. The disruption of the educational process generates great frustration for former child soldiers. Therefore, all reintegration and rehabilitation programs must invest time and resources to ensure that these children have secured their training until the end.